STUDENTS’ BEHAVIOURAL PATTERNS ON BACHELOR’S DEGREE CHOICES IN SRI LANKA: HEURISTICS? - Abeygunawardena, K. A. Vidyanjalie (PEOPLE: International Journal of Social Sciences, 2019)
At present National university intake in Sri Lanka has become progressively competitive due to the limited number of placements. Consequently, several private higher educational institutes (PHEIs) in Sri Lanka entered into the higher education market with various international degree programmes of top-ranked foreign universities to cater to the need of university-level education in Sri Lanka. Therefore, this study attempts to uncover the behavioural patterns of students in selecting a Bachelor’s degree (BD) from International Degree Programmes which emerged recently in Sri Lanka. Subsequently, the data for the study were collected by 420 first-year students of International Degree Programmes by administering a questionnaire with 59 predefined variables. Of those, 36 variables and 42 variables were identified as the most influential variables by factor analysis for the male and female group respectively. Thereby, it has determined that ’marketing strategy’, ’university characteristics’, ’infrastructure facilities’, ’programme evaluation’ and ’reputation of the university’ were the common influential factors for both the groups but with different orders of importance. Alternatively, the ’peer’ and ’sources of information’ are rated as influential in selecting a BD only by the male group. Even though the female group have not remarked any ’information sources’ as influential, they rated the ’first impression’ of the PHEI impact them in selecting the BD. However, ’financial support’ and ’cost’ are influential factors for the male group while ’cost’ is not imperative for the female students in selecting their BD. Finally, higher education student-choice model was developed based on the heuristics of Sri Lankan students. Indeed the results of this study can be beneficial in optimising the enrolment strategies of PHEIs in Sri Lanka and in guiding prospective students on their BD choices in higher education.